Implementasi Peraturan Daerah Nomor 4 Tahun 2018 Tentang Rencana Pembangunan Industri Provinsi Sumatera Utara Tahun 2018 - 2038 Pada Dinas Perindustrian dan Perdagangan Provinsi Sumatera Utara - Halizah Indriyanti; Warjio Warjio; Budi Hartono (Mahesa Research Center, 2022)
Purpose to find out and analyze the implementation and what factors hinder and support the implementation of Regional Regulation Number 4 of 2018 concerning the Industrial Development Plan of North Sumatra Province for 2018-2038 at the Industry and Trade Office of North Sumatra Province. This research is a descriptive study with a qualitative approach. For the analysis, the implementation theory that the researcher uses is the implementation theory of Edward III. Based on Edward III's Theory, indicators affecting implementation are: Communication, Resources, Disposition and Bureaucratic Structure. Communication implementation has not run optimally. Implementation resources have not been informed and carried out optimally, Disposition in the implementation of implementation has been carried out properly. In the Bureaucratic Arrangement, it is still running less than optimally or seems slow because. There are no awards in the form of incentives for implementation implementers. The bureaucratic structure has been running well and has complied with the applicable provisions in order to support the implementation of the Regional Regulation concerning the Provincial Industrial Development Plan. The fragmentation in the implementation of the Perda RPIP has gone well, marked by the North Sumatra Province Industry and Trade Office with other technical services within the North Sumatra Provincial Government.